Angeletics: Philosophical and Christian Ethical Implications - Molotokienė, Ernesta (International Journal of Current Innovations in Advanced Research, 2023)
The christian ethics of Thomas Aquinas meets the present need for an intercultural new media ethics as angeletics developed by one of the most famous current theorist Rafael Capurro dealing with problematic field of media ethics that transcends the legal realm by linking the ideas of justice and virtue in an ingenious way. Thomas’s virtue theory coordinates private and public activities through a set of context-invariant, justice-oriented norms with conceptual appeal to contemporary questions of intercultural new media ethics. In our article, we first sketch how Aquinas’s theory can be also of relevance to a non-confessional (virtual) audience through its appeal to the ‘natural light of reason.’ Then we explain how his theory of ‘natural law’ aligns his ideas of virtue and justice. From this vantage point, we address the tension between cultural diversity and moral uniformity in the sphere of new medi ethics in general and in today’s globalized angeletics in particular. Throughout the article, we aim to show how thomistic ethics gains inter-personal and inter-cultural validity that establishes social justice as the global virtue of angeletics.